-2.4(y+0.2)=-0.3(y+1.6)

Simple and best practice solution for -2.4(y+0.2)=-0.3(y+1.6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2.4(y+0.2)=-0.3(y+1.6) equation:


Simplifying
-2.4(y + 0.2) = -0.3(y + 1.6)

Reorder the terms:
-2.4(0.2 + y) = -0.3(y + 1.6)
(0.2 * -2.4 + y * -2.4) = -0.3(y + 1.6)
(-0.48 + -2.4y) = -0.3(y + 1.6)

Reorder the terms:
-0.48 + -2.4y = -0.3(1.6 + y)
-0.48 + -2.4y = (1.6 * -0.3 + y * -0.3)
-0.48 + -2.4y = (-0.48 + -0.3y)

Add '0.48' to each side of the equation.
-0.48 + 0.48 + -2.4y = -0.48 + 0.48 + -0.3y

Combine like terms: -0.48 + 0.48 = 0.00
0.00 + -2.4y = -0.48 + 0.48 + -0.3y
-2.4y = -0.48 + 0.48 + -0.3y

Combine like terms: -0.48 + 0.48 = 0.00
-2.4y = 0.00 + -0.3y
-2.4y = -0.3y

Solving
-2.4y = -0.3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '0.3y' to each side of the equation.
-2.4y + 0.3y = -0.3y + 0.3y

Combine like terms: -2.4y + 0.3y = -2.1y
-2.1y = -0.3y + 0.3y

Combine like terms: -0.3y + 0.3y = 0.0
-2.1y = 0.0

Divide each side by '-2.1'.
y = 0

Simplifying
y = 0

See similar equations:

| 2x^2-15=0 | | -0.7y-0.6=-0.2y+3.4 | | -3(3w+4)=-9w+6 | | .125v+.5=.875v+3.5 | | 6m+8=35 | | -9v+12=-3v-18 | | 6(x-3)=4(9+3x)-6x | | -10=12x+x | | (-4x)(0.5r)= | | 9(x+1)=5-2(9x+6) | | 30=5x+25 | | 37x+3=6(6x+4) | | -23=-6w-11 | | v^2-3v+2=0 | | 2x^2+5-3= | | 3(6-4x)=(-6x+9) | | -1x+5=2x-2 | | 3x-3=4+2x-6 | | 9y+10-7y-1= | | -2x+3=x-2 | | y=5x-3 y=-2x4 | | -8(x-1)-4(3-x)=-14 | | 6(x+2)=3(2x+8)-12 | | 5+6y=6y+35-4y | | 5y+7+3y=6 | | 2-3x=6x-4x-38 | | 7x+8=3x-12 | | 5x+4y=23 | | 12y=-8x+0 | | A-b=c-a-1 | | 2y=3x+2 | | -3.3(-2g-9)+3.9g= |

Equations solver categories